Impact of Revitalisation on the Tourist Attractiveness of the City - Anna GARDZINSKA; Agnieszka SAWINSKA (Communications of International Proceedings, 2020)
Revitalisation contributes to the social and economic development of degraded urban areas. Moreover, the issue of revitalisation is addressed in terms of competition between cities over potential tourists. The revitalisation of urban areas improves the image of the area, ensures free use of the renewed rest and recreation zones by residents and tourists and contributes to the increase of tourist attractiveness. The area attractive for tourists in which revitalisation activities are undertaken is the city of Szczecin. The main aim of the article is to evaluate the process of revitalisation in Szczecin by the inhabitants of the city and to indicate its impact on tourist attractiveness. The diagnostic survey method was used to assess the impact. The survey was conducted using the CAWI technique among the members of social networking services associating the residents of Szczecin. The obtained results enabled the determination whether the city's residents notice the changes taking place in the city as a result of revitalisation activities and how they assess these changes as well as their impact on the tourist attractiveness of Szczecin.
Keywords: Revitalisation; Tourist Attractiveness; Tourism; City.